Distinción entre conocimiento léxico y vocabulario en la didáctica del inglés. Revisión bibliográfica (Memorias Sifored - Encuentros Educación UAN, 2022)
This article makes a bibliographic review about the concept of lexical knowledge and vocabulary in the recent literature of the didactics of English. Methodology: a bibliographic review was carried out based on the search for materials in the Google Scholar search engine, in the Dialnet, Scielo and Redalyc databases, and in the ResearchGate academic network. Results: 30 articles published in the period 2016 to 2021 in indexed journals and 10 master's and doctoral theses are analyzed, with 30% of the materials being in English and the remaining 70% in Spanish. Two trends are identified when it comes to addressing lexical knowledge and vocabulary, which affect the way English didactics are developed. Conclusions: the importance of distinguishing between the concept of lexical knowledge and that of vocabulary is established, being that the latter refers to understanding the meanings of a word and is evaluated from the volume of words, while lexical knowledge focuses on the contextual meaning and placement of a word in the particular linguistic structure of the English language.
Keywords: Learning; Acquisition Lexical competence; English Language; Semantics